Formulation of Business Strategy at Faeyza Gallery Store with Porter's Swot & Fives Forces Analysis Approach (Descriptive Analysis Study of Live Streaming Sales Competitiveness) - Wahyudin, Gildian Rahadian; Tantri, Prisilia Angel; Abrori, Imam (International Journal of Accounting and Management Research, 2025)
This study aims to determine the role of SWOT analysis and Porter's Five Forces in increasing the competitiveness of Toko Faeyza Gallery in the live streaming sales business at Shopee. This research uses a qualitative approach with data collection methods in the form of observation, interviews, and documentation. Data analysis was carried out descriptively with data validity tested through source triangulation. The results showed that: (1) The SWOT analysis applied includes an assessment of strengths, weaknesses, opportunities, and threats. Based on the IFAS and EFAS matrix calculations, a score of 1.40 and 0.50 was obtained, respectively. This position shows that Toko Faeyza Gallery is in quadrant I (progressive), which means that the live streaming strategy at Shopee has significant strengths that can be utilized to encourage business growth. (2) Porter's Five Forces analysis shows that this method is relevant for recognizing barriers to new entrants, bargaining power of suppliers and buyers, potential substitute products, and intensity of competition. These results provide constructive strategic guidance for Toko Faeyza Gallery in formulating strategies to compete effectively in the digital marketplace.